Miniaturized Negative-Pressure Wound Therapy for Split-Thickness Skin Graft Donor Sites - Mitchell, Stuart L.; Ray, Edward; Cordeiro, Peter G. (Journal of Reconstructive Microsurgery Open, 2018)
Background Multiple therapeutic options exist for the treatment of split-thickness skin graft (STSG) donor sites, but there is no clear consensus among surgeons about the best option. Negative-pressure wound therapy (NPWT) has rapidly gained in popularity since its invention. Recently, several miniaturized, single-patient NPWT (SP-NPWT) devices have become available. Compared with traditional NPWT devices, SP-NPWT devices are associated with equal wound healing capability and reliability, but offer several advantages. We present a series of 10 consecutive patients whose STSG donor sites were treated with a commercially available SP-NPWT device.Methods We performed a retrospective review for 10 consecutive patients who underwent STSG procedures and were treated with SP-NPWT devices.Results From 2015 to 2017, 10 consecutive patients underwent oncologic reconstruction using STSG and had their donor sites treated with SP-NPWT devices. The SP-NPWT dressing had been left in place for 2 weeks after surgery. The average donor site area measured 80 cm2 (range: 76–106 cm2). In all 10 patients, the donor sites healed uneventfully and with no complications.Conclusion Off-the-shelf, miniaturized, SP-NPWT systems appear to be at least as effective as traditional dressings for STSG donor sites and require no maintenance (skilled nursing or dressing changes). Compared with larger and less portable standard NPWT devices, SP-NPWT dressing systems provide a potential cost benefit as well as enhanced convenience and portability.
Keywords: single-patient negative-pressure wound therapy; split-thickness skin graft donor site; vacuum-assisted closure; PICO single-use NPWT system